2009
DOI: 10.1128/mcb.00229-09
|View full text |Cite
|
Sign up to set email alerts
|

Organization of F-Actin via Concerted Regulation of Kette by PTP61F and dAbl

Abstract: We identify Kette, a key regulator of actin polymerization, as a substrate for Drosophila protein tyrosine phosphatase PTP61F, as well as for dAbl tyrosine kinase. We further show that dAbl is a direct substrate for PTP61F. Therefore, Kette phosphotyrosine levels are regulated both directly and indirectly by PTP61F. Kette and PTP61F genetically interact in the regulation of F-actin organization in pupal eye discs, suggesting that tyrosine phosphorylation is essential for the proper regulation of Kette-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…To examine the subcellular localization of PTP52F, we performed immunofluorescence staining with PTP52F antibody together with F‐actin co‐staining in S2 cells attached to the lectin concanavalin A (ConA) substrate. When spreading on the ConA‐coated surface, cortical actin structure in S2 cells would be concentrated at the cell periphery, thus allowing us to determine the leading edge of the plasma membrane as demonstrated in our previous study [39]. Using F‐actin staining as the guidance, we have observed that the ectopically expressed WT form of PTP52F is highly enriched near the plasma membrane (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…To examine the subcellular localization of PTP52F, we performed immunofluorescence staining with PTP52F antibody together with F‐actin co‐staining in S2 cells attached to the lectin concanavalin A (ConA) substrate. When spreading on the ConA‐coated surface, cortical actin structure in S2 cells would be concentrated at the cell periphery, thus allowing us to determine the leading edge of the plasma membrane as demonstrated in our previous study [39]. Using F‐actin staining as the guidance, we have observed that the ectopically expressed WT form of PTP52F is highly enriched near the plasma membrane (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…However, we cannot exclude the possibility that PTP61Fn may in part elicit its effects by acting downstream of receptor PTKs, or indeed through direct effects on the Ras/MAPK pathway, as recent studies suggest that PTP61F may act on MAPK itself [46]. Downstream PTKs that may be dephosphorylated by PTP61F include the Abl PTK, with previous studies suggesting that Abl may mediate EGFR signalling in flies, and that Abl can serve as a direct substrate of PTP61F to regulate actin organisation [46,64]. Yet another potential downstream tyrosine phosphorylation-dependent pathway by which PTP61Fn may mediate its effects on receptor PTK signalling is the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that the PTP61F-mediated repression of PVR-, but promotion of the Dockinduced overgrowth may be elicited via independent pathways. Dock and PTP61F may have opposing roles in actin polymerisation [63,64,75,76]. Perhaps in the activated PVR background, the coexpression of PTP61Fm with Dock, which itself is tyrosine phosphorylated by Src42A and dephosphorylated by PTP61F [77], perturbs actin polymerisation to influence tissue growth [78].…”
Section: Discussionmentioning
confidence: 99%
“…PTP61F, the Drosophila ortholog of human PTP1B and TCPTP, has been reported to interact with Dock, an adapter protein required for axon guidance (Clemens et al, 1996). PTP61F has recently been shown to coordinate with dAbl in regulating actin cytoskeleton organization via reversible tyrosine phosphorylation of Abi and Kette (Huang et al, 2007;Ku et al, 2009). Moreover, dPtpmeg, a FERM and PDZ domaincontaining NT-PTP, is reported to be involved in the formation of neuronal circuits in the Drosophila brain (Whited et al, 2007), though its molecular function in this process is not known.…”
Section: Introductionmentioning
confidence: 99%